Characterization of the microstructure and hardness of case-carburized gear steel. (May 2021) - Chen, Wu; He, Xiaofei; Yu, Wenchao; Shi, Jie; Wang, Maoqiu; Yao, Kefu
Highlights: The carburized case of the experimental steel had a multiphase microstructure consisting of martensite, carbides and evenly retained austenite. The nano-hardness decreased from about 12 GPa in the near-surface case to about 7 GPa in the core, while the microhardness decreases from 800 HV0.2 to 450 HV0.2, with the ratio of nano-hardness to microhardness to be constant of about 15. Pop-ins could be found on load-displacement curves due to phase transformation of retained austenite. Abstract: The microstructure and hardness of case-hardened steel were investigated after carburizing and austenitizing at 820−900 °C, and oil quenching and tempering at 180 °C. The carburized case had a multiphase microstructure consisting of martensite, carbides, and retained austenite, and the maximum content of the retained austenite was 30%; the particle size range was 2–3 μm. The nano-hardness decreased from about 12 GPa near the surface to about 7 GPa in the core, and the microhardness decreased from 800 HV0.2 to 450 HV0.2 . The in-depth distribution of the microhardness and nano-hardness showed a similar trend, and the ratio of nano-hardness to microhardness was about 15. The results were attributed to the fine particle size of the retained austenite and its even distribution in the martensite matrix and it could not lower the nano-hardness. The nano-hardness was relatively low in areas of the retained austenite (about 5.5 GPa), and pop-in effects were observed, indicating the phase transformation of the retained austenite during nanoindentation loading.